Bioherbisida Pra Tumbuh Rimpang Alang-Alang (Imperata cylindrica) untuk Pengendalian Gulma di Areal Perkebunan Kelapa Sawit - Vira Irma Sari; Dody Boy Lorensha; Ratih Rahhutami (JURNAL CITRA WIDYA EDUKASI, 2021)
Imperata cylindrica contains allelochemical compounds that could be used as natural active inggredients to control weeds, especially the rhizome. Bioherbicide pre-emergence was expected to be able controlling weeds from germination so that the population of weeds will be reduced later. The objectives of this experiment were to obtain the alternative material for pre-emergence bioherbicide, to know the effectivity of pre-emergence Imperata cylindrica to growth, height and biomass of weeds, and also identify the dominant weeds in treatment area. This research conducted at Teaching Farm Politeknik Kelapa Sawit Citra Widya Edukasi Bekasi, from Januari until Juli 2021. This research was arranged in a factorial random block design with three replications and five treatments. The treatments are P0 (Control), P1 (Herbisida 1%), P2 (Bioherbicide 5%), P3 (Bioherbicide 10%), P4 (Bioherbicide 15%). Each of treatments repeated three times, so that there were 15 experimental unit. The data was analysis of variance. If the analysis variance test result was significant at 5%, then it continued by Least Significance Different Test (LSD Test). The result showed Imperata cylindrica could be as alternative material for pre-emergence bioherbicide and significantly affected to weed’s growth in 1 until 2 weeks after application (WAP), and heigt’s weed in 3 WAP. The lowest weed’s growth showed in control and not significantly different with all treatments. The weed dominance it showed in area is Axonopus compressus. The allelochemical compound contained in pre-emergence bioherbicide Imperata cylindrica are flavonoids 0,097% and tanin 0,105%.